1993
DOI: 10.2500/105065893781976447
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year follow-up after Limited Anterior Functional Endoscopic Sinus Surgery (FESS)

Abstract: This paper describes clinical outcomes in patients who underwent FESS. The subjects included 64 patients with chronic sinusitis, ranging in age from 11 to 66 years. A total of 44 (68%) underwent bilateral FESS, 16 (25%) underwent unilateral FESS, and 4 (7%) had anterior-posterior removal of tissue. No major complications occurred and minor complications occurred in eight patients (12.3%). At 6 months follow-up. 86% of 57 patients were belter. 12% were unchanged, and one patient (1.7%) was worse. After 2 years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…The removal of a narrowed or obstructed ostiomeatal complex that impedes the natural cleaning forces of cilia is the primary goal in functional endoscopic sinus surgery (FESS) [1]. However, it is known that the population of cilia in the maxillary sinus mucosa can sometimes be reduced in CS [10].…”
Section: Introductionmentioning
confidence: 99%
“…The removal of a narrowed or obstructed ostiomeatal complex that impedes the natural cleaning forces of cilia is the primary goal in functional endoscopic sinus surgery (FESS) [1]. However, it is known that the population of cilia in the maxillary sinus mucosa can sometimes be reduced in CS [10].…”
Section: Introductionmentioning
confidence: 99%
“…In our series, no patient reported worsening of their condition following surgery. Several other studies claim that some patients were worse off following surgery 18,35 . It may be possible at this stage to speculate that some patients are worse off by more aggressive surgery, which may interfere with nasosinus drainage.…”
Section: Discussionmentioning
confidence: 92%
“…17 Austin et al showed a statistically significant relation to an improved outcome in FESS with septoplasty. 18 They reported an incidence of 42% septal deviation in their series of 64 patients. Damm et al have reported septoplasty rates of 71% in their 279 cases with FESS.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations